How to communicate IAM in water losses and energy management – the experience of a collaborative project - Ribeiro, R. (2015)
Water utilities have to deal with different challenges including ageing infrastructures, climate change and increased societal expectations. The ISO 50 000 and 55 000 standards are effective tools for implementing procedures by which organizations can work strategically on energy and infrastructure asset management systems, respectively. The implementation success of these management systems is determined by the reliability and availability of information and the capacity of water utilities to progress in the direction of sharing knowledge and skills, breaking down information silos and boundaries resulting from functional specialism. Collaboration is essential to achieve improvements in the long term. This paper aims to outline potential synergies between collaborative knowledge production and the implementation of structured approaches to increase water services sustainability. In the iPerdas2014 project, 17 Portuguese water utilities developed their own water losses and energy management plan following a joint training and capacitation approach. Results indicate that the use of a collective problem framing and a defined framework for decision making allows working strategically with water losses and energy efficiency issues, with a clear integration in the infrastructure asset management system. Straightforward communication since day one is critical to achieve top management support and staff involvement, establishing conditions for continuous improvement.